Impact of Interest Margin, Market Power and Diversification Strategy on Banking Stability: Evidence from ASEAN-4 - Bustaman, Yosman; Ekaputra, Irwan Adi; A. Husodo, Zaafri; Prijadi, Ruslan (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research Paper Research aims: This study aims to examine the impact of interest margin, market power and banking diversification strategy in products and loan portfolios on banking stability in the ASEAN-4 countries (Indonesia, Malaysia, Thailand and the Philippines). Design/ Methodology/ Approach: The long-term equilibrium is examined with the random effect panel data regression model while the short-term dynamic relationship between the variables is examined through the dynamic panel data regression model, System Generalized Method of Moment (GMM). Research findings: After controlling foreign bank penetration, bankspecific variables and macroeconomic variables, this study finds that the intermediary activities which generate interest margins remain as a dominating factor that promotes banking stability in ASEAN-4. This study also finds pure fee-based income products can help banks to reduce instability although an increase in trading activities tend to reduce stability. Additionally, focused-banks which channel special types of loans may charge a higher margin thereby, lowering the banks’ probability of default. An increase in market power, as an impact on banking consolidation, increases banking stability. This finding is consistent with the “competition fragility” hypothesis. However, this is unable to support the non-linear relationship between competition and banking stability. Theoretical contributions/ Originality: This study contributes to literature by examining the combined effect of interest margin, market power and revenue and loan portfolio diversification on banking stability in ASEAN-4 Practitioner/ Policy implications: Product diversification increases banking stability but banks need to exercise a prudent approach in executing trading activities. The lack of expertise in these activities will increase banking instability. Regulators should scrutinise the cartel-formation behaviour of larger banks so as to encourage more competition and avoid instability in the banking industry. Research limitations/ Implications: This research applies common practices in the measurement of banking stability namely, the Z score. Future studies may use a combination of data drawn from capital market capitalisations of bank assets and market stability to measure the modified Z score as a means to assess market feedback.